Development of Paramadina Roomhub Application As Room Booking System Using Waterfall Method - Maulana, Reza Arif; Fatih, Muhamad Adillah; Suto, Lintang Arbi; Darwis, Muhammad (JISA(Jurnal Informatika dan Sains), 2024)
The manual room booking process at Paramadina University faces several challenges, including inefficiencies, human errors, and communication breakdowns between applicants and facility managers. These issues often result in room booking conflicts and delays, hindering effective facility usage. The need for a more streamlined, user-friendly solution led to the development of the Roomhub Paramadina application, a web-based system designed to facilitate room bookings within the university. The objective of this research is to design and implement a digital room booking system that simplifies the current manual process. The application was developed using the Software Development Life Cycle (SDLC) with the Waterfall framework. This approach ensures structured and systematic development, enabling the team to follow sequential stages from requirements gathering to testing. The Roomhub application allows users to view available rooms, submit booking requests, and receive confirmations directly via an online platform. The system integrates with existing university infrastructure and ensures real-time room availability, reducing errors such as double bookings. Black-box testing was employed to verify the application’s functionality, and the results confirmed that the system meets user needs while significantly improving booking efficiency. By automating room bookings and enhancing communication between the parties involved, this research offers a practical solution that improves operational efficiency, reduces paperwork, and minimizes scheduling conflicts, thereby benefiting the entire academic community at Paramadina University.